2018
DOI: 10.3390/nu10081073
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and Utilization of Three Nutritional Supplements during Pregnancy: Findings from a Longitudinal, Mixed-Methods Study in Niger

Abstract: Nutritional status in pregnancy is a key determinant of birth outcomes. In low-income countries, maternal diets are often limited, and daily nutrient supplements are recommended to fill nutrient gaps. As a result, it is important to understand the factors influencing acceptability and utilization of nutrient supplements in these settings. Qualitative data (individual interviews and focus group discussions with pregnant women, household members, and study staff) and quantitative data (unannounced household spot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 29 publications
(48 reference statements)
4
17
0
Order By: Relevance
“…Our medium-term compliance results for both supplements were similar to the median self-reported compliance of small quantity lipid-based nutrient supplements (LNS) for pregnancy of 83.7% and 93.8% in Ghana and Malawi, respectively (Klevor et al, 2016). An increase in self-reported compliance over time was seen in other long-term adherence studies of supplements in pregnant women in Niger (Clermont et al, 2018) and Malawi (Klevor et al, 2016). Similar to our findings, the women reported getting used to the product as one factor for increased compliance (Clermont et al, 2018).…”
Section: Supplement Choicesupporting
confidence: 79%
See 1 more Smart Citation
“…Our medium-term compliance results for both supplements were similar to the median self-reported compliance of small quantity lipid-based nutrient supplements (LNS) for pregnancy of 83.7% and 93.8% in Ghana and Malawi, respectively (Klevor et al, 2016). An increase in self-reported compliance over time was seen in other long-term adherence studies of supplements in pregnant women in Niger (Clermont et al, 2018) and Malawi (Klevor et al, 2016). Similar to our findings, the women reported getting used to the product as one factor for increased compliance (Clermont et al, 2018).…”
Section: Supplement Choicesupporting
confidence: 79%
“…Support from family members and healthcare professionals could also play a key role in compliance and uptake of supplements. In Niger, health workers played an important role in sensitizing women and their families, thus increasing the acceptance of the supplements (Clermont et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Common outcomes presented in LQR publications are themes (and how they change across time), intervention development/evaluation, or conceptual pathways. For example, Clermont et al (2018) were able to identify themes that explained decreased utilization of nutrient supplements in pregnant women despite their stated high level of acceptance. Mean-while, Corepal et al (2018) used their qualitative study to better understand how and why an intervention designed to promote physical activity was effective among a group of adolescents.…”
Section: Results Of Longitudinal Qualitative Researchmentioning
confidence: 99%
“…Our findings that MQ-LNS improved WLZ at 1 mo of age relative to IFA are consistent with this hypothesis of a better nutritional environment in utero. Another potential explanation is that there was a higher propensity to share MQ-LNS with other household members or substituting it for food ( 27 ) and therefore the actual micronutrient intake in the MQ-LNS arm may have been lower than planned. Additional research is needed to understand the mechanisms that may lead to transient differences in anthropometric outcomes in children whose mothers receive prenatal MQ-LNS as compared with MMS or IFA.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed nutritional composition of the 3 study supplements is shown in Supplemental Table 1 . Formative work conducted prior to the start of the trial showed that the 3 supplements were well accepted by the communities and pregnant women ( 27 ).…”
Section: Methodsmentioning
confidence: 99%